THE ACQUISITION OF CONCEPTUAL UNDERSTANDING OF HISTORICAL THINKING IN THE CONTEXT OF MULTI ETHNIC STUDENTS IN MALAYSIA - Ahmad, Abdul Razaq (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2010)
This study related to previous studies emphasizing the importance of conceptual understanding towards the improvement of the historical thinking process. It was aimed at finding out how ethnical elements influence the acquisition of students’ conceptual understanding in history as well as observing the differences and the correlation between multi-ethnic students’ conceptual understanding level and the historical thinking aspects. This study was a survey study using instruments of tests and interviews with students based on stratified sampling taken from the whole Malay Peninsula comprising four zones of North Zone (21.9%), South Zone (22.1%), Central Zone (34.0%) and East Zone (22.0%). The rating scale for conceptual understanding and historical thinking was excellent, good, fair, and poor. The test items used within the test were based on the curriculum of history for Sekolah Menengah Tingkatan Empat (Form Four of Secondary School) including early civilization, South East civilization, Islamic civilization and European civilization. Theories from experts were considered in the composition of test items and in order to ensure the reliability of the result. Interviews were also conducted to get teachers’ response to the teaching of conceptual understanding and historical thinking. Six teachers were chosen for the interview. the data shows that students’ conceptual understanding level was fair in general (mean=3.07, s.p = 1.103) where the historical thinking was poor (mean = 1.94, s.p = 0.834). Students’ conceptual understanding level will affect their thinking ability and analysis towards the subject matter. Malay students were different significantly in conceptual understanding and history thinking from the Chinese and Indian ones. The clarity of instruction showed a high correlation with conceptual understanding while learning activities showed a high correlation with historical thinking.